A policy study on environmental protection in the Philippines - Magtolis, Carlos M. Jr (Philippine journal of public administration)
Environmental protection in the Philippines presents an arduous and complex history from the colonial period up to the present. Environmental policies used to cater to natural resources conservation according to the controls imposed by colonial powers. A gradual shift toward pollution control started in the 1960s in response to the adverse effects of industrialization, and followed by succeeding Presidential Decrees mandating a comprehensive and integral program in environmental protection issued during Martial Law. In 1990s, the Ramos administration created the Philippine Council for Sustainable Development and formulated the Philippine Agenda 21. The Clean Air Act was enacted in 1999. At present, environmental sustainability is enshrined in the Millennium Development Goals (MDGs) and the Medium Term Philippine Development Plan (MTPDP). Despite an extensive array of environmental laws, the Philippine environmental condition continues to deteriorate with constant controversies on mining revitalization, poor implementation, budgetary constraints, weak monitoring and enforcement, and lack of political will. This article traces the important elements in the evolution of Philippine public administration in line with the policies, laws and institutional formulations on environmental protection vis-a-vis the challenges to improve governance.